Obsidian Provenance Data Reveals New Insights into Archaic Lifeways in Chihuahua, Mexico. (2nd October 2019) - Dolan, Sean G.; Gallaga, Emiliano; Shackley, M. Steven
ABSTRACT: Archaeologists know less about how hunter-gatherers and early agriculturists lived during the Archaic period in the Mexican Northwest compared to the U.S. Southwest. To evaluate Archaic period mobility, lithic technology, and regional and temporal patterns in raw material procurement in northwestern Chihuahua, Mexico, we characterized the trace elemental composition of 61 obsidian artifacts from Rancho Santa María I, II, and El Peñón del Diablo using energy-dispersive X-ray fluorescence spectrometry. People predominantly used Los Jagüeyes obsidian procured locally from secondary deposits, but they also used three additional sources from upland and lowland environments in the Mexican Northwest to make dart projectile points and debitage. Also, they reduced obsidian using bipolar percussion, and there is regional and temporal variation in obsidian source use. This study contributes new insights into how mobility, raw material availability, and nodule size affected lithic technological organization in an understudied region.